KAJIAN MODEL MATEMATIS KINETIKA INAKTIVASI ENZIM LIPOKSIGENASE UNTUK PRODUKSI TEPUNG BIJI KECIPIR SEBAGAI TEPUNG KOMPOSIT - D. K. wikanta; Mohamad Endy Yulianto; I. Hartati (JURNAL ILMIAH MOMENTUM, 2010)
Winged bean (Psophocarpus tetragonolobus L) which its nutrition content is similar to soybean, is expected as the substitute of soybean. Winged bean can be used as source of protein by transforming it into composite flour which can be used as food product or edible film in food packaging. The utilization of winged bean is limited caused by its strong bitter beany flavour. The beany flavour is caused by the conversion of unsaturated fatty acid especially linoleate that catalyzed by lipoksigenase. In order to avoid the beany flavour, it’s urge to find an appropriate method which able to extract the oil of winged bean in the low or zero activity of lipoksigenase. In order to avoid the conversion of hydroperoxide fatty acid, we need to develop an effective extraction method which inactivate the lipoksigenase and also separate the unsaturated fatty acid in winged bean. The purpose of the present study is to develop the kinetics models of the lipoxygenation enzyme inactivation in winged bean flour production. The kinetics models can be described as first orde reaction and it is depends on pressure, temperature and water concentration. Keywords: enzyme, inactivation, winged bean